Discovery of Lysine-Targeted eIF4E Inhibitors through Covalent Docking - Wan, Xiaobo (J Am Chem Soc, 2020)
Eukaryotic translation initiation factor 4E (eIF4E) binds the m7GTP cap structure at the 5′-end of mRNAs, stimulating the translation of proteins implicated in cancer cell growth and metastasis. eIF4E is a notoriously challenging target, and most of the reported inhibitors are negatively charged guanine analogues with negligible cell permeability. To overcome these challenges, we envisioned a covalent targeting strategy. As there are no cysteines near the eIF4E cap binding site, we developed a covalent docking approach focused on lysine. Taking advantage of a “make-on-demand” virtual library, we used covalent docking to identify arylsulfonyl fluorides that target a noncatalytic lysine (Lys162) in eIF4E. Guided by cocrystal structures, we elaborated arylsulfonyl fluoride 2 to 12, which to our knowledge is the first covalent eIF4E inhibitor with cellular activity. In addition to providing a new tool for acutely inactivating eIF4E in cells, our computational approach may offer a general strategy for developing selective lysine-targeted covalent ligands.